Development and validation of a nomogram to predict indolent course in patients with ulcerative colitis: a single-center retrospective study. (30th June 2022) - Li, Na; Zhan, Shukai; Liu, Caiguang; Li, Tong; Tu, Tong; Chen, Baili; He, Yao; Chen, Minhu; Zeng, Zhirong; Zhuang, Xiaojun
Abstract: Background: The natural disease course for patients with ulcerative colitis (UC) is heterogeneous and few data are available on the indolent course of UC and its related factors. We aimed to develop and validate a nomogram to predict indolent course in patients with UC. Methods: Data of patients diagnosed with UC in the First Affiliated Hospital of Sun Yat-sen University (Guangzhou, China) between April 2007 and February 2021 were retrospectively analysed. Indolent course was defined as a disease course without need for strict interventions (steroids, immunomodulators, biological agents, hospitalization, or surgery therapy) during the follow-up period. The whole cohort was randomly divided into training set and validation set. The nomogram was constructed in the training set based on the results of univariate and multivariate Cox regression analyses. The performance of the nomogram was assessed by the concordance index (C-index), area under the receiver-operating characteristic curve (AUC), and calibration plots. In addition, we internally validated the nomogram via the bootstrap method and the validation set. Results: Of 969 treatment-naive patients with UC, 771 (79.6%) had an indolent course after diagnosis. Of these, 313 patients were included in the development and validation of the nomogram. The nomogram incorporating age, disease activity, C-reactive protein, and platelet count showed good calibration and discrimination. The C-index was 0.759 (0.741 in bootstrap validation) and the AUC at 2, 4, and 6 years was 0.767, 0.782, and 0.775, respectively. The nomogram performed well when applied to the validation set. Conclusion: A majority of patients with UC had an indolent course after diagnosis. The nomogram developed in this study might be useful in therapeutic decision-making and follow-up management for patients with UC.